(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This paper contains a series of philosophical reflections that try to tie together certain aspects of the functioning of the human brain with recent findings in physics, psychology and the cognitive sciences. The thesis is that the articulation of these findings validates the generation of theoretical constructs that might prove to be useful for enriching the approach to and interpretation of the social sciences and humanities. Examples are proposed that demonstrate the applicability of these constructs for interpreting contemporary historical and cultural developments by carefully considering their own relativity as an instrument as well as their future potential.